Le site rupestre de Qorqor (Gar‘āltā, Éthiopie) entre littérature et peinture. Introduction à l’édition de la Vie et des miracles de saint Daniel de Qorqor et aux recherches en cours - Claire Bosc-Tiessé (Afriques)
This introduction to the edition and translation into French of an unpublished Geez text, the Life and Miracles of Saint Daniel of Qorqor, presents the current research on the Qorqor rock-hewn site in Northern Ethiopia. Questioning methods and documents at our disposal to construct the history of the site as a prelude to that of the actual Christianization of the region, it provides a first comparative reading of data provided by the text and by the inscriptions on the paintings.